Production of biopolymer from waste materials as the suitable alternative for plastics - Rohaida, Che Man; Nur Nadia, Mohd Zakaria; Nurul Nabila Huda, Baharudin (CRC Press, 2022)
Biopolymer is a promising alternative material to substitute synthetic plastics for daily use, due to its excellent stability, biocompatibility, and biodegradability. This chapter discusses the current investigations on the production of polyhydroxyalkanoates (PHA) using wastes from different sources such as lipid, milk, and agricultural waste. The utilization of these wastes reduces the production cost for the sustainable production of eco-friendly biopolymer. Recent developments in the fermentation process and optimization of process parameters contribute toward the research effort on managing the waste for biopolymer production. Biopolymer applications in industries are highlighted as well. Moreover, limitations and future prospects for biodegradable and low-cost biopolymer production are addressed.